Purple Hibiscus - Ngozi, Chimamanda Adichie (Nigeria, 2018)
When Nigeria is shaken by a military coup, kambili's father, involoved mysteriously in the political crisis,sends her to live with her aunt. In this house, noisy and full of laughter, she discovers life and love - and a terrible, bruising secret deep within her family
Keywords: Family; Juvenile Fiction